2016
DOI: 10.1590/s1984-29612016026
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Rhipicephalus (Boophilus) microplus (Acari: Ixodidae) resistance to different acaricide formulations using samples from Brazilian properties

Abstract: The Rhipicephalus (Boophilus) microplus tick is responsible for considerable economic losses in Brazil, causing leather damage, weight loss and reduced milk production in cattle and results in the transmission of pathogens. Currently, the main method for controlling this tick is using acaricides, but their indiscriminate use is one of the major causes of resistance dissemination. In this study, the adult immersion test (AIT) was used to evaluate resistance in ticks from 28 properties located in five different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(23 citation statements)
references
References 15 publications
3
18
0
2
Order By: Relevance
“…In countries with well-developed systems of agricultural pesticide regulation, there is a little chance that the manipulation of acaricide concentration will ever be an option as a method to delay the emergence of resistance, because legislation generally prescribes their use only at the acaricide concentrations specified on their label (Guerrero et al 2014 ). However, in some developing countries, acaricide concentrations are manipulated by farmers from time to time (Higa et al 2016 ).…”
Section: Strategies To Minimize the Development Progression And Impamentioning
confidence: 99%
“…In countries with well-developed systems of agricultural pesticide regulation, there is a little chance that the manipulation of acaricide concentration will ever be an option as a method to delay the emergence of resistance, because legislation generally prescribes their use only at the acaricide concentrations specified on their label (Guerrero et al 2014 ). However, in some developing countries, acaricide concentrations are manipulated by farmers from time to time (Higa et al 2016 ).…”
Section: Strategies To Minimize the Development Progression And Impamentioning
confidence: 99%
“…If we were to consider only the efficacy results of product 1 in the field, excluding the in vitro test, product 1 could be considered ineffective in tick control because of the low efficacy values presented. According to studies by Gomes et al (2011) and Higa et al (2016) in the same region of the study were found populations resistant to this acaricide formulation.…”
Section: Discussionmentioning
confidence: 80%
“…In this context, the Brangus cross showed superiority with respect to Nellore and other crosses in this region (Battistelli et al, 2013); however, cross-bred animals are generally more susceptible to ticks, and the control of these ectoparasites is achieved through the use of acaricides. This increase in infection pressure places these populations of ticks at a higher risk of developing resistance, including multi-chemical resistance to the different chemical bases used (Higa et al, 2015) in different regions (Andreotti et al, 2011, Higa et al, 2016, Klafke et al, 2017 of Brazil. Another aggravating factor in the use of acaricides is the risk of environmental contamination and residues in meat, milk and its derivatives (De Meneghi et al, 2016, Gaus and Furlong, 2002, Kunz and Kemp, 1994.…”
Section: Introductionmentioning
confidence: 99%
“…(B.) microplus to the chemical acaricides available in the market are alarming (Higa et al, 2016;Klafke et al, 2017;Raynal et al, 2013). In the search for new drugs, substances of plant origin have demonstrated high efficacy in vitro and can be associated with commercial products to prolong the efficacy by reducing the selective pressure for development of resistant tick strains (Chagas, 2015;Roel, 2001).…”
Section: Introductionmentioning
confidence: 99%